PENGARUH KUALITAS KEHIDUPAN KERJA, PEMBERDAYAAN DAN KOMPENSASI TERHADAP KEPUASAN KERJA (STUDY EMPIRIS PADA PT.SANGO CERAMICS INDONESIA) - Yanu Prafitasari, 13.05.51.0146 (Students Journal of Economic and Management, 2017)
The purpose of this study is to investigate the influence of quality of work life, empowerment and compensation on job satisfaction. The object of this research at the PT.Sango Ceramics Indonesia. The sampling technique in this research use the purposive sampling technique with 85 respondents. Data collected through questionnaires. Technique analysis of the data used include the test validity, reliability testing with Alpha Cronbrach, multiple regression analysis, T test to test and approve the research hypothesis. The results of the research that quality of work life has positive and significant effect on job satisfaction, the stronger quality of work life within the employee, will improve satisfaction in employee the organization. Empowerment and significant positive effect on job satisfaction, the more employees feel empowered by the organization, the level of employee satisfaction wiil increase. Compensation and significant positive effect on job satisfaction, that the more just and true way of distributing compensation to employees, will improve stronger satisfaction to reach organization target. Keywords : Quality of Work Life , Empowerment, Compensation and Job Satisfaction